Answer:
![\frac{9}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B9%7D%7B4%7D)
Step-by-step explanation:
Given
x² - 3x
To make the expression a perfect square
add ( half the coefficient of the x- term )²
x² + 2( -
)x +
, thus
x² - 3x + ![\frac{9}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B9%7D%7B4%7D)
= (x -
)² ← a perfect square
Answer:
dependent events since P(A and B) is not equal to P(A) * P(B)
Step-by-step explanation:
According to the Question,
- Given, The probability that Jane will go to a ballgame (event A) on a Monday is 0.73, and the probability that Kate will go to a ballgame (event B) the same day is 0.61. The probability that Kate and Jane both go to the ballgame on Monday is 0.52.
Thus, The events A, B and A∩B are:
A - Jane will go to a ballgame on Monday;
B - Kate will go to a ballgame on Monday;
A∩B - Kate and Jane both go to the ballgame on Monday.
- P(A)=0.73, P(B)=0.61, P(A∩B)=0.52.
- Pr(A)⋅Pr(B) = 0.73⋅0.61 = 0.4453 ≠ 0.52
So, events A and B are dependent events since P(A and B) is not equal to P(A) * P(B)
=(f-g)(x)
=f(x)-g(x)
=x+6-(x-6)
=x+6-x+6
=12
Answer: -2, 0, 4
Set the equation equal to zero.
x³ - 2x² - 8x = 0
Factor out x in the equation, since all the terms (x³, -2x², and -8x) are divisible by x. You can check your accuracy using the Distributive Property.
x(x² - 2x - 8) = 0
Factor out the polynomial. To do this, find two numbers that multiply to get the last term, -8, and add together to get the middle term, -2. In this case, those two numbers are -4 and 2 (-4 × 2 = -8 and -4 + 2 = -2). Don't forget about the x that was factored out before!
x(x - 4)(x + 2) = 0
Set each factor equal to zero and solve for x. The factors in the equation are x, (x - 4), and (x + 2).
x = 4
x = -2
The zeros of the polynomial function are -2, 0, and 4.
Answer:
D 150 ft is the length of 5 ft